A phosphorus-doped potassium peroxyniobate electrocatalyst with enriched oxygen vacancies boosts electrocatalytic nitrogen reduction to ammonia. Issue 29 (8th July 2022) - Fan, Shuhui; Zhao, Fei; Wang, Xuansheng; Wang, Qi; Zhao, Qiang; Li, Jinping; Liu, Guang
Abstract : A KNb3 O8 electrocatalyst with phosphorus doping and abundant oxygen vacancy presents a rate of 23.01 μg h −1 mgcat −1 for NH3 production at −0.45 VRHE and an FE of 39.77% at −0.4 VRHE in 0.1 M Na2 SO4 electrolyte under ambient conditions. Abstract : The electrochemical ammonia synthesis is an environmentally friendly method for ammonia production; however, it is still impeded by the bottleneck of N2 activation and challenging hydrogen evolution reaction (HER). A rational design for developing efficient electrocatalysts by tuning the surface electronic state is regarded as a promising strategy to overcome these obstacles. Herein, we report a phosphorus-doped potassium peroxyniobate (KNb3 O8, denoted as P-KNO) electrocatalyst with enriched oxygen vacancies to effectively improve N2 -to-NH3 efficiency and suppress HER. Such P-KNO electrocatalyst achieves a rate of 23.01 μg h −1 mgcat −1 for NH3 production at −0.45 V vs. reversible hydrogen electrode (RHE) and a faradaic efficiency (FE) of 39.77% at −0.4 VRHE in a 0.1 M Na2 SO4 electrolyte, which is about twice that of the non-modified KNb3 O8 (denoted as KNO, 11.35 μg h −1 mgcat −1, 19.60%) counterpart under the same condition. Moreover, the resultant P-KNO electrocatalyst renders steady NH3 yield amounts and selectivity in cycling tests for 10 h. It is concluded that the enhanced N2 fixation activity and faradaic efficiency are ascribed to the phosphorus doping and formation of oxygen vacancies, which not only make the surface of the electrocatalyst highly hydrophobic but also adjust the surface electronic structure of potassium niobate, thus resulting in accelerated N2 adsorption and activation during the NRR process. This electrocatalyst with phosphorus-doping and oxygen vacancies gives deep insights into the rational regulation of the surface electronic state of NRR electrocatalysts for efficient NH3 synthesis.